International Experience in the Development of Green Economy - DENISSOVA, Oxana; KOZLOVA, Marina; RAKHIMBERDINOVA, Madina; VARAVIN, Yevgeniy; ORDABAYEVA, Mainur (Journal of Environmental Management and Tourism, 2018)
This paper describes the concept of "green economy" and the stages of its formation. The foreign experience of reforming the economy on the principles of "green" growth is generalized and systematized and the possibilities of its use in the conditions of the Republic of Kazakhstan are determined. The assessment of the effectiveness of the development policy in Kazakhstan from the standpoint of compliance with the principles of "green" growth is given.